1982
DOI: 10.1021/jm00345a011
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting enzyme inhibitors: importance of the amide carbonyl of mercaptoacyl amino acids for hydrogen bonding to the enzyme

Abstract: A series of mercaptoacyl amino acids and related compounds was synthesized and evaluated for inhibition of angiotensin-converting enzyme (ACE) in order to determine the nature and importance of the putative interaction between ACE and the amide moiety of inhibitors such as captopril (3-mercapto-2-methylpropanoyl-L-proline). It was concluded that the interaction involves a hydrogen bond from a donor site on ACE to the oxygen of the amide carbonyl. Compounds in which the amide moiety is replaced by other groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…These compounds can be thought of as partial analogues of the inhibitor glycyl-L-phenylalanine, IC50 = 630/M , with the peptide bond replaced by an ethylene bridge. Replacement of the peptide bond by an ethylene bridge usually causes a large decrease in inhibitory potency (Condon et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…These compounds can be thought of as partial analogues of the inhibitor glycyl-L-phenylalanine, IC50 = 630/M , with the peptide bond replaced by an ethylene bridge. Replacement of the peptide bond by an ethylene bridge usually causes a large decrease in inhibitory potency (Condon et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The absorbance is proportional to the H 2 O 2 level, which is decreased by catalase as it degrades the H 2 O 2 . Values were expressed in μmol H 2 O 2 /min/mg 46.…”
mentioning
confidence: 99%
“…Preliminary experiments, data not shown, revealed that the immediate attachment of vinyl dimethylazlactone at multi thiol‐functional PO X copolymers through radical mediated as well as Michael addition‐based thiol–ene reaction led to cross‐linking of the individual dissolved polymer chains, which was to be expected since attached azlactone rings can be easily opened by remaining thiols of the polymer side chains. Hence, a new mercaptoacyl amino acid, N ‐(3‐mercapto‐1‐oxopropyl)‐2‐methyl‐alanine (MOMA), based on the non‐proteinogenic amino acid 2‐aminoisobutyric acid was synthesized adapted from Condon et al to overcome this problem. The synthesis is a two‐step approach, in the first step, the amine group of the amino acid is transformed into an amide by addition of 3‐bromopropionyl chloride and a thioester is introduced through the addition of thiobenzoic acid in a slightly alkaline environment.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of MOMA is a two‐step synthesis adopted from Condon et al to produce mercaptoacyl amino acids. The first step is the synthesis of N ‐[3‐(benzoylthio)‐1‐oxopropyl]‐2‐methylalanine, which is deprotected in the second step to reveal the free thiol.…”
Section: Methodsmentioning
confidence: 99%